2018
DOI: 10.1177/2333392818792169
|View full text |Cite
|
Sign up to set email alerts
|

General Practitioners’ Barriers Toward Medication Reviews in Polymedicated Multimorbid Patients

Abstract: Purpose:The aim of this study was to explore whether general practitioners (GPs) experienced barriers toward medication reviews in polymedicated, multimorbid patients, and how a clinical pharmacologist with a focus on pharmacotherapy can support the GPs in an outpatient clinic.Design:The study was descriptive and exploratory and had a qualitative design with a phenomenological/hermeneutic orientation for the interviews.Participants:The study comprised 14 interviews with 14 different GPs from the Capital Region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…A recent survey conducted in Denmark has shown that general practitioners are often left alone in the management of polypharmacy set up in hospitals [8]. Also in our study, it emerged that it is unfortunately common that the specialist prescribes following the guidelines without considering the patient's age, the comorbidities and the risks associated with polypharmacy.…”
Section: Introductionmentioning
confidence: 72%
“…A recent survey conducted in Denmark has shown that general practitioners are often left alone in the management of polypharmacy set up in hospitals [8]. Also in our study, it emerged that it is unfortunately common that the specialist prescribes following the guidelines without considering the patient's age, the comorbidities and the risks associated with polypharmacy.…”
Section: Introductionmentioning
confidence: 72%
“…Fourteen individual countries were represented across the 33 studies: Netherlands [48][49][50][51][52][53][54], England [55][56][57][58][59], Australia [60][61][62][63], Denmark [64][65][66][67], Norway [50,[67][68][69], Ireland [70][71][72], New Zealand [73][74][75], Canada [76,77], Wales [50,69], Sweden [67,78], Finland [67], Iceland [67], Portugal [79] and Scotland [80]. Together these studies included a total of 593 unique GP participants (range: 4-74 GPs).…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
“…Studies focused on multimorbidity were usually oriented towards a particular aspect of multimorbidity care. Some used the broad lens of 'patient management,' [48,53,55,59,63,67,72,[77][78][79][80] while others focused on medication management [51,52,60,62,66,70,71,73,74]; clinical practice guidelines [49,58,61,68]; GP decision making [50,69,75]; care goals [54,76]; patient selfcare [57,64]; disease management programs [65]; and health service orientation [56].…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
“…Combined with a lack of communication between physicians, this may lead to increase harm from polypharmacy [7,15]. In these qualitative studies, many GPs call for better interprofessional communication and a fair balance between them and specialists when sharing prescribing activity [15,16]. Our quantitative study con rmed that cooperation and con dence between physicians is not obvious for a majority of GPs (moderate and low cooperation pro les).…”
Section: Comparison With Literaturementioning
confidence: 69%
“…Accordingly, health policies in several countries encourage interprofessional cooperation and multiprofessional practices (e.g., multidisciplinary or multiprofessional group practices and healthcare networks) [12][13][14]. Several qualitative studies have addressed these professionals' experiences and perceptions of such cooperation [7,15,16]. But little is known about how and the extent to which GPs cooperate with other healthcare professionals (medical specialists and non-physician professionals as pharmacists, nurses, physical therapists etc) and in managing patients with multimorbidity and polypharmacy, and whether their propensity to cooperate may in uence their own practices.…”
Section: Introductionmentioning
confidence: 99%